Financial constraints in China: firm-level evidence - Sandra Poncet; Walter Steingress; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper uses a unique micro-level data-set on Chinese firms to test for the existence of a "political-pecking order" in the allocation of credit. Our findings are threefold. Firstly, private Chinese firms are credit constrained while State-owned firms and foreign-owned firms in China are not; Secondly, the geographical and sectoral presence of foreign capital alleviates credit constraints faced by private Chinese firms. Thirdly, geographical and sectoral presence of state firms aggravates financial constraints for private Chinese firms ('crowding out?. Therefore it seems that ongoing restructuring of the state-owned sector and further liberalization of foreign capital inflows in China can help to circumvent financial constraints and can boost the investment of private firms.
Keywords: E22; G32; 330; Investment-cashflow sensitivity; China; firm level data; foreign direct investment; Unternehmenserfolg; Öffentliches Unternehmen; Privatwirtschaft; Multinationales Unternehmen; Verschuldungsrestriktion; Kapitalimport; China